2019
DOI: 10.21608/jssae.2019.53685
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Behavior of Natural Minerals along with Synthetic Soil Conditioners on Nutritional Status and Yield Productivity

Abstract: A field experiment was carried out for two successive seasons (summer season 2017 and winter season 2017/2018) on sandy soil at Ismailia Agric. Res. Station, Ismailia Governorate, Egypt (Latitude, 30˚35' 41.901" N and longitude, 32˚16' 45.834" E) cultivated with sesame and wheat crops respectively, to highlight the effect of applying natural minerals and synthetic soil conditioners alone or in combined on some sandy soil properties and productivity of sesame and wheat crops. Three natural clay minerals (benton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Clinoptilolites are synthetic substances with high cation exchange properties with the potential to retain ammonium ions (Jakkula and Wani, 2018). Hydrogel, polyvinyl alcohol, and anionic polyacrylamide are soil conditioners reported by Seddik et al (2019) noticed to increase the total nitrogen content of the soil. Although, according to Youssef et al (2019), polyvinyl alcohol had no significant effect on the nitrification process.…”
Section: Other Agrochemicals and Substancementioning
confidence: 99%
“…Clinoptilolites are synthetic substances with high cation exchange properties with the potential to retain ammonium ions (Jakkula and Wani, 2018). Hydrogel, polyvinyl alcohol, and anionic polyacrylamide are soil conditioners reported by Seddik et al (2019) noticed to increase the total nitrogen content of the soil. Although, according to Youssef et al (2019), polyvinyl alcohol had no significant effect on the nitrification process.…”
Section: Other Agrochemicals and Substancementioning
confidence: 99%
“…Dahri et al (2019) found that Superabsorbent Polymers (SAP) in powder and crystal forms decreased soil bulk density, increasing porosity and field capacity. Seddik et al (2019) showed synthetic soil conditioners improved soil properties, enhancing field capacity and nutrient availability, positively impacting plant growth and yield in sesame and wheat.…”
Section: B Field Capacity (Fc)mentioning
confidence: 99%
“…This group will include amendments like biochar, superabsorbent polymer (SAP), nonwoven geotextiles, water absorbing geocomposite (WAG) or biodegradable water absorbing geocomposite (bioWAG). Their function is to retain additional amounts of water in the soil profile through a reduction of water infiltration or evaporation [1][2][3][4][5][6]. Water conservation is essential due to the high level of water consumption for agricultural purposes and progressing climate change.…”
Section: Introductionmentioning
confidence: 99%